KELIMPAHAN SPESIES DAN PRODUKSI BAHAN KERING HIJAUAN PAKAN KELINCI DI KABUPATEN PANIAI - Sawen, Diana; Rahayu, B.W. Irianti (Pastura; Vol 5 No 1 (2015): Pastura Vol. 5 No. 1 Tahun 2015DO - 10.24843/Pastura.2015.v05.i01.p05, 2015)
The potential forage largely determines the success of the development of a ruminants farm. This study aims to find out how much abundance and production of dry matter forage of rabbits. The study was conducted for one month in the District of East Paniai and Tigi in Paniai Regency, analysis of dry matter at the Laboratory of Animal Nutrition and Feed FPPK UNIPA Manokwari, using descriptive method with survey techniques and field observations. This study shows that there are five species of grasses, 5 species of non forage and 4 types of food crops which is consumed by the rabbit with fresh forage production is 4600 gram/ m2. Dry matter production of 5630.71 gram/m2 and dry matter percentage of 23.56%., while the legume species was not found. Key words: species abundance, dry matter, rabbit forage